A new species of the Neotropical genus Daimothoracodes Petrovitz (Coleoptera: Scarabaeoidea: Hybosoridae) - Ocampo, Federico C. (Zootaxa, 2005)
Daimothoracodes rugomarginatus Ocampo, new species, is described from Distrito Federal, Brazil. A key to the four known species of the genus is provided in English and Spanish, and a distribution map is provided with a new country record of D. magnificus for Argentina.Se describe a Daimothoracodes rugomarginatus Ocampo, especie nueva, basada en ejemplares de Brasil, Distrito Federal. Se provee una clave en Inglés y Español para las cuatro especies conocidas, y se provee un mapa de la distribución de las especies de Daimothoracodes con un nuevo registro de D. magnificus para Argentina.